Effect of swarnamrithaprashana on promotion of immunity in children: A randomized double-blind clinical trial - Shailaja Uppinakuduru; S Nayan Kumar; Prasanna Narasimha Rao; G R Arun Raj (Wolters Kluwer Medknow Publications, 2021)
Introduction: To evaluate the effect of Swarnamrithaprashana on immunity (Bala) and general health status in children. Methods: The present study was a randomized double-blind placebo-controlled interventional prospective clinical trial wherein 221 healthy children within the age group of 6-12 years were enrolled from the schools of Hassan town. Registered children received one soft gel capsule in trial group - Swarnamrithaprashana (containing 2 mg of swarnabhasma) and in control group - sugar syrup, in morning empty stomach along with luke warm water for a duration of 30 days. Assessment of the effect of treatment was done by observing the changes seen in serum immunoglobulin G and salivary immunoglobulin A after 60 days of initiation of treatment as primary outcome parameter and changes in anthropometrical parameters, dehabala, agnibala, and manobala as secondary outcome measures. Renal function test (RFT) and liver function tests (LFTs) were done before and after treatment for assuring safety of the formulation. Results: The trial group showed better decrease in serum and salivary immunoglobulin levels, indicating a decrease in immunoglobulin recruitment in circulation, but the changes were not statistically significant at P = 0.05. The trial group showed better improvement in parameters suggesting Dehabala, Agnibala, and Manobala, which were statistically significant at P = 0.05. There were no significant changes seen in RFT and LFT values done before and after the treatment. Conclusion: Though the changes observed in the levels of immunoglobulins were not statistically significant in the present study setup, Swarnamrithaprashana helps in improving immunity at the level of immunoglobulins. Swarnamrithaprashana was found to be effective in the promotion of immunity in children reflected by improvements in parameters representing dehabala, manobala, and agnibala in children. The formulation was found to be safe as there were no signs of hepato and nephrotoxicity in RFT and LFT.